Determinants of the development venture financing of the subjects of agrarian market of Ukraine - Trusova, Natalia; Трусова, Наталя Вікторівна; Трусова, Наталья Викторовна; Tanklevska, N. S.; Prystеmskyi, O. S.; Hryvkivska, O. V.; Advokatova, N. O. (My University, 2019)
The article substantiates the determinants of the development of the Ukrainian venture industryin agriculture, taking info account the comprehensive melhodological approach to ensuring the profitability of financial assets of agricultural market subjects in the distribution of investment resourees of venture funds.
Keywords: venture funds; venture capital; investment resources; innovations; agriculture; agrarian enterprises; Ukraine